1984
DOI: 10.1016/0014-5793(84)80205-7
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphoinositide hydrolysis by phospholipase C is accelerated by thyrotropin releasing hormone (TRH) in clonal rat pituitary cells (GH3 cells)

Abstract: Thyrotropin releasing hormone (TRH) accelerates the turnover of phosphatrdylinosrtol m GH3 cells ('phospholiprd response') From the analysis of inositol phosphates m the presence of Li+ which inhibits their dephosphorylatron, rt can be concluded that the hydrolysis of phosphatidylmosrtol4,5-biphosphate, and possibly of phosphatidylinosrtol 4-phosphate by phospholipase C 1s markedly accelerated by TRH. It appears that this reaction initiates the acceleratron of phosphatrdylinositol turnover. The specificity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Under basal conditions, IPi and IP2 repre¬ sented approximately 98% of the inositol polyphosphates, and the non-stimulated level of IP3 was very low. Several studies have demonstrated that lithium blocks inositol 1-phosphomonoesterase (for review see Berridge, Downes & Hanley, 1989) and induces accumulation of inositol polyphosphates in GH3 cells Schlegel, Roduit & Zahnd, 1984). In our model, addition of 10 mmol LiCl/1 enhanced the concentration of all inositol phosphates.…”
Section: Effect Of Trh On A-msh Secretionmentioning
confidence: 99%
“…Under basal conditions, IPi and IP2 repre¬ sented approximately 98% of the inositol polyphosphates, and the non-stimulated level of IP3 was very low. Several studies have demonstrated that lithium blocks inositol 1-phosphomonoesterase (for review see Berridge, Downes & Hanley, 1989) and induces accumulation of inositol polyphosphates in GH3 cells Schlegel, Roduit & Zahnd, 1984). In our model, addition of 10 mmol LiCl/1 enhanced the concentration of all inositol phosphates.…”
Section: Effect Of Trh On A-msh Secretionmentioning
confidence: 99%
“…Taken together these findings suggest that a GTP binding protein similar or identical to Ni is involved in the coupling of receptors to enhanced PIP2 breakdown. We and others have shown that TRH, similar to fMLP in neutrophils, acts in GH3 cells to enhance PIP2 hydraiysis by phospholipase C, generating IFS ] [18][19][20][21] which in turn mubilizes Ca2+ from intracellular stores [22,23]_ A further aim of this study was therefore to investigate whether FT would affect the Ca" mobilizing action of TRH in GH3 cells.…”
Section: Introductionmentioning
confidence: 99%
“…23). Patch pipettes had an average resistance of [1][2][3][4][5] Mfl (open diameter, 1-3 ,um). Recording of currents was usually started 5 min after disruption of the membrane patch for intracellular dialysis with the pipette solution.…”
mentioning
confidence: 99%